CERITA Al-Qur an untuk anak Tim Penulis EFK ; editor, Danu Nugraha, Umi Andriani, Singgih Agung ; ilustrator, Iwan Nazif - Nugraha, Danu; Andriani, Umi; Agung, Singgih; Nazif, Iwan (Erlangga, 2007)
176 hlm. : ilus. ; 25 cm.